Local Political Dynamics in the Development of Ecotourism in Barru Regency in 2025 - Asril, Muh.; Nadir, Sakinah; Imran, Muh (Journal of Cultural Analysis and Social Change, 2026)
This study examines the involvement of local government actors in the development of ecotourism in Barru Regency, South Sulawesi. Ecotourism, as defined by Law Number 10 of 2009 and Minister of Home Affairs Regulation Number 33 of 2009, emphasizes the balance between environmental conservation, community empowerment, and economic growth. Despite Barru’s rich natural potential, the implementation of ecotourism policies remains suboptimal due to limited human resources, weak institutional coordination, and the absence of specific local regulations. Using a qualitative descriptive approach, this study reveals that local government plays a central role in planning, facilitating, and regulating ecotourism activities; however, the effectiveness of these roles is constrained by bureaucratic and financial challenges. Strengthening collaboration among government institutions, the private sector, and local communities is essential to achieving sustainable ecotourism development. The findings recommend that the Barru Regency Government formulate a regional regulation on sustainable ecotourism as a strategic step to harmonize national and local policies, promote participatory governance, and enhance the welfare of local communities through environmentally responsible tourism.